An Optimal Data Fusion Approach for Precise Position Estimation of Smartphone User: An Optimal Data Fusion Approach for Precise Position Estimation of Smartphone User - Jamil, Harun (Journal of Intelligent Pervasive and Soft Computing, 2023)
This paper proposes an optimal data fusion approach for precise position estimation of smartphone users in challenging environments, combining BLE-based indoor position estimation and PDR using smartphone sensors. The approach utilizes RSSI values from nearby BLE beacons for BLE-based estimations and employs PDR with an accelerometer, magnetometer, and gyrometer for position orientation. These observations are then fed into an ANN for accurate position prediction, and Particle Filter is used for probabilistic pedestrian position prediction. Experimental results demonstrate improved accuracy compared to individual techniques, making the approach robust for accurate smartphone user positioning in challenging environments.